Penjerapan Natrium pada Hasil Ekstraksi Silika dari Lumpur Panas Bumi - Akmal, Afiffurroyan Aflah; Purnomo, Chandra Wahyu; Ariyanto, Teguh (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Geothermal sludge contains silica which can be used as plant fertilizer. Extraction of silica from geothermal sludge can be carried out by the extraction method using sodium hydroxide solution to form sodium silicate. This extraction was conducted by varying the extraction time of 10, 20, 30, 40, 50, 60, 70 and 80 minutes; NaOH concentration of 1,5N; and extraction temperature of 80oC. Extracted silica concentration was analyzed using UV-Vis Spectrophotometry. The best extracted silica content was 158673 ppm under 60 minutes of extraction time, 80oC of extraction temperature, and 1.5N of NaOH concentration. The results of this extraction still contain sodium at a concentration and need to be reduced so that it can be used as fertilizer. The process of reducing sodium concentration using the ion exchange method in a batch system. This process uses variations of initial sodium concentration with a resin mass of 20 grams and temperature of 45oC. From the Atomic Adsorption Spectroscopy (AAS) analysis, the adsorption capacity (qe) increases with increasing the initial sodium concentration. Langmuir's equilibrium provide a match to the adsorption equilibrium experimental data.